The Pattern of Morphine Necessity for Acute Renal Colic Patients in the Emergency Department; A Cross-Sectional Observational Prospective Study - Elahe Karimpour-Razkenari; Yasaman Borhani; Kamal Basiri; Farhad Najmeddin; Hooshyar Honarmand; Arash Safaei (Journal of Pharmaceutical Care, 2023)
Background: Renal colic is one of the most common urologic diseases that constitutes the majority of the emergency department (ED) patients. Intravenous ketorolac is usually prescribed for adequate pain control, but it is usually insufficient and morphine is required. The starting time and amount of morphine needed for acute renal colic is still under discussion. Methods: This prospective, observational study was conducted for 6 months at ED of Sina hospital, Tehran, Iran. 44 patients were investigated. pain intensity with numeric rating scale (NRS) were observed at baseline and then continued every 5 min for 2hr. Patients were received ketorolac (30 mg) and if NRS>6 morphine loading dose (0.05mg/kg) initially if NRS>6. morphine rescue dose ordered if the NRS remain >6. Morphine consumption pattern was the primary outcome. Also total morphine dose, time to reach NRS<4, and adverse reaction were evaluated. Results: At baseline, almost all patients had NRS>6, and about 65.8% had history of renal colic. The mean NRS was 8.98(±0.98), Therefore, all patients required a loading dose of morphine and 50% received at least one rescue dose. The patient with history of renal colic had higher NRS score at baseline, prolonged pain, higher total morphine dose and rescue dose. There wasn’t any significant side effect occurred. Conclusion: Patients with acute renal colic have severe pain and should receive morphine primarily. In addition, patients with a history of renal colic had higher pain intensity scores, and required higher morphine doses.